Diversifying Groundnut Products: Empowering the Kulo Farmers Group with Peanut Milk and Butter - Hairana, Hairana; Novita, Sri; Susanti, Anisa; Ahmad Mahbub, Itang; Hidayatur Rohman, M. Akbar (Jurnal Karya Abdi Masyarakat, 2024)
Groundnut (Arachis hypogaea) is one of the leading agricultural commodities in Teluk Village, Pemayung Subdistrict. The local variety, Garuda, is characterized by its large size and high yield potential, typically producing 3–4 seeds per pod. Despite its potential, the commodity is commonly sold only in raw form, limiting its economic value. This community engagement project aimed to empower the Kulo Farmers Group by diversifying groundnut-based products into peanut milk and peanut butter. The program was implemented through the Student Organization Capacity Building Program (PPK Ormawa Tymac), with the university serving as a facilitator of knowledge and technology transfer. Activities included product development, business registration (NIB), intellectual property rights (IPR) facilitation, partnership building, and the creation of a digital marketing platform via Shopee. The Participatory Rural Appraisal (PRA) approach was applied to ensure that activities were tailored to the actual needs and capacities of the community. As a result, the farmers gained practical skills in food processing and entrepreneurship, and the value of local groundnuts increased through product innovation. This program demonstrated that academic–community collaboration can enhance local economic resilience. Continued mentoring and market expansion are recommended to sustain the initiative’s impact.